Odpowiedź :
Odpowiedź:
[tex]a)\ \ \sqrt[3]{3^3+4^3+5^3}=\sqrt[3]{27+64+125}=\sqrt[3]{216}=6\\\\b)\ \ \sqrt[3]{6^3+3^3+10^2}=\sqrt[3]{216+27+100}=\sqrt[3]{343}=7\\\\c)\ \ \sqrt[3]{14^2-13^2}=\sqrt[3]{196-169}=\sqrt[3]{27}=3\\\\d)\ \ \sqrt[3]{4+\sqrt[3]{64}}=\sqrt[3]{4+4}=\sqrt[3]{8}=2[/tex]
[tex]a) \ \sqrt[3]{3^{3}+4^{3}+5^{3}}=\sqrt[3]{27 + 64+125} = \sqrt[3]{216} = \sqrt[3]{6^{3}} = 6[/tex]
[tex]b) \ \sqrt[3]{6^{3}+3^{3}+10^{2}} =\sqrt[3]{216 + 27+100} = \sqrt[3]{343} = \sqrt[3]{7^{3}} = 7[/tex]
[tex]c) \ \sqrt[3]{14^{2}-13^{2}} =\sqrt[3]{(14+13)(14-13)} = \sqrt[3]{27\cdot1} = \sqrt[3]{27} = \sqrt[3]{3^{3}} = 3[/tex]
[tex]d) \ \sqrt[3]{4+\sqrt[3]{64}}} = \sqrt[3]{4+4} = \sqrt[3]{8} = \sqrt[3]{2^{3}} = 2[/tex]